2010
DOI: 10.1021/nn1005599
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Inhibition of C-26 Colon Carcinoma by VSVMP Gene Delivered by Biodegradable Cationic Nanogel Derived from Polyethyleneimine

Abstract: Biodegradable cationic nanoparticles have promising application as a gene delivery system. In this article, heparin−polyethyleneimine (HPEI) nanogels were prepared, and these nanogels were developed as a nonviral gene vector. The transfection efficiency of HPEI nanogels was comparable with that of PEI25K, while the cytotoxicity was lower than that of PEI2K and much lower than that of PEI25K in vitro. These HPEI nanogels also had better blood compatibility than PEI25K. After intravenous administration, HPEI nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 50 publications
2
106
0
Order By: Relevance
“…The non-viral vectors, such as cationic lipids and polymers have many advantages over viral ones: low immunogenicity, easy to produce and no limitation to the size of transferred DNA molecules, but the toxicity is still a hindrance for the application of non-viral vectors in gene therapy (21,23,24). Polyethylenimine (PEI), one of the most successful and widely studied gene delivery cationic polymers, is effective in gene delivery on account of its condensation of DNA, which facilitates endocytosis, and 'proton sponger' quality, which can prevent DNA from endosomal disruption (25,31). Because PEI is not biodegradable and has the shortcoming of an association between transfection efficiency and cytotoxicity (25,26), in our previous study, the low molecular weight PEI was conjugated chemically into biodegradable cationic nanogels by heparin, to develop a novel gene Figure 5.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The non-viral vectors, such as cationic lipids and polymers have many advantages over viral ones: low immunogenicity, easy to produce and no limitation to the size of transferred DNA molecules, but the toxicity is still a hindrance for the application of non-viral vectors in gene therapy (21,23,24). Polyethylenimine (PEI), one of the most successful and widely studied gene delivery cationic polymers, is effective in gene delivery on account of its condensation of DNA, which facilitates endocytosis, and 'proton sponger' quality, which can prevent DNA from endosomal disruption (25,31). Because PEI is not biodegradable and has the shortcoming of an association between transfection efficiency and cytotoxicity (25,26), in our previous study, the low molecular weight PEI was conjugated chemically into biodegradable cationic nanogels by heparin, to develop a novel gene Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…delivery vector (31,32). HPEI nanogels were quickly degraded into low molecular weight PEI followed by excretion through urine in vivo and they also exhibited better blood compatibility, lower cytotoxicity, and stability in vitro, therefore, we used HPEI nanogels as the gene carrier in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kong et al (70) found that IRDye900-conjugated pullulan-cholesterol nanoprobe NIR-PNG exhibited the favorable characteristics of lower dispersion and longer retention in the SLN compared to diluted indocyanine green (ICG) and ICG/poly-γ-glutamic acid complex following injection into the stomachs of dogs and pigs (70). Nanogels may be controlled for various applications in drug delivery and may be tailored to exhibit exceptional stability, low cytotoxicity and higher blood compatibility (71,72). Nanogels containing 5-fluorouracil (5-FU) were developed to be utilized as a new colon-targeting drug carrier systems, owing to their excellent pH-sensitive release property and effectively reduced toxicity (73).…”
Section: Nanogelsmentioning
confidence: 99%